Agenda Setting in Social Networks and the Media during Presidential Elections - Duche-Pérez, Aleixandre Brian; Vera-Revilla, Cintya Yadira; Medina Rivas Plata, Anthony Rolando; Gutiérrez-Aguilar, Olger Albino; Hillpa-Zuñiga, Manuel Edmundo; Escobar Juárez, Antonio Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article examines the role of social media and journalistic media in presidential electoral processes. A systematic review of scientific articles published from 2012 to 2022 was conducted. The results indicate that the media has a significant influence on public perception and the political agenda during election campaigns. Furthermore, the importance of evaluating political leaders in the voters' decision-making process is emphasized. In summary, the article provides valuable insights into how the media can shape the narrative and public opinion during presidential elections.